Protein decomplexation and proteomics: A complementary assessment method of the physicochemical purity of antivenom. (January 2021) - Tan, Choo Hock; Liew, Jia Lee; Chong, Ho Phin; Tan, Nget Hong
Abstract: The quality of antivenom is governed by its safety and efficacy profiles. These quality characteristics are much influenced by the purity of antivenom content. Rigorous assessment and meticulous monitoring of antivenom purity at the preclinical setting is hence crucial. This study aimed to explore an integrative proteomic method to assess the physicochemical purity of four commercially available antivenoms in the region. The antivenoms were subjected to Superdex 200 HR 10/30 size-exclusion fast-protein liquid chromatography (SE-FPLC). The proteins in each fraction were trypsin-digested and analyzed by nano-ESI-liquid chromatography-tandem mass spectrometry (LC-MS/MS). SE-FPLC resolved the antivenom proteins into three major protein components of very high (>200 kDa), high (100–120 kDa) and medium (<60 kDa) molecular weights. The major components (80–95% of total proteins) in the antivenoms were proteins of 100–120 kDa consisting of mainly the light and partially digested heavy immunoglobulin chains, consistent with F(ab')2 as the active principle of the antivenoms. However, LC-MS/MS also detected substantial quantity of large proteins (e.g. alpha-2-macroglobulins), immunoglobulin aggregates and impurities e.g. albumins in some products. The method is practical and able to unveil the quantitative and qualitative aspects of antivenom protein compositions. It is therefore a potentially useful preclinical assessment tool of antivenom purity. Highlights: The protein compositions of four antivenom products were assessed. Antivenom proteins were fractionated with size-exclusion liquid chromatography. Proteins were profiled by nano-ESI-liquid chromatography-tandem mass spectrometry. Bioactive principles and impurities were examined qualitatively and quantitatively. The integrative method is potentially useful in quality control of antivenom purity.